2018
DOI: 10.1002/jcp.26284
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‐200b/miR‐429 contributes to neuropathic pain development through targeting zinc finger E box binding protein‐1

Abstract: Many studies have reported that microRNAs participate in neuropathic pain development. Previously, miR-200b and miR-429 are reported to be involved in various diseases. In our current study, we focused on their roles in neuropathic pain and we found that miR-200b and miR-429 were significantly decreased in chronic constriction injury (CCI) rat spinal cords and isolated microglials. miR-200b and miR-429 overexpression were able to relieve neuropathic pain through modulating PWT and PWL in CCI rats. Meanwhile, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…XIST can accelerate neuropathic pain progression through the regulation of miR‐150 and ZEB1 in CCI rat models. miR‐200b/miR‐429 can participate in neuropathic pain development by targeting Zeb1 . In our current study, we observed that Zeb1 was elevated in CCI rats.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…XIST can accelerate neuropathic pain progression through the regulation of miR‐150 and ZEB1 in CCI rat models. miR‐200b/miR‐429 can participate in neuropathic pain development by targeting Zeb1 . In our current study, we observed that Zeb1 was elevated in CCI rats.…”
Section: Discussionsupporting
confidence: 55%
“…33 I n addition, recently, Zeb1 has been reported to be involved in neuropathic pain development. 34,35 XIST can accelerate neuropathic pain progression through the regulation of miR-150 and ZEB1 in CCI rat models. miR-200b/miR-429 can participate in neuropathic pain development by targeting Zeb1.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐155 can regulate inflammation response through SOCS1–STAT3–PDCD4 in atherogenesis (Ye et al, ). LncRNA MEG3 can regulate ischemic neuronal death via targeting miR‐21/PDCD4 (H. Yan, Rao et al, ; X. T. Yan, Zhao et al, ). MiR‐499 can protect endothelial cells against inflammatory damage by inhibiting NF‐κB/TNF‐α by targeting PDCD4 in coronary artery disease (Y. H. Zhang, He, & Shi, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time several miRNAs, such as miR-200b and miR-429, are down-regulated in microglia after nerve injury, and Zeb1 (Zinc finger E-box binding homeobox 1) has been identified as a target of these two miRNAs [109]. Zeb family members are essential for the developing nociceptors in the DRG [138].…”
Section: Mirnas Deregulated In the Peripheral Nervementioning
confidence: 99%